Genome-wide association study of circulating interleukin 6 levels identifies novel loci - Ahluwalia Tarunveer S; Prins Bram P; Abdollahi Mohammadreza; Armstrong Nicola J; Aslibekyan Stella; Bain Lisa; Jefferis Barbara; Baumert Jens; Beekman Marian; Ben-Shlomo Yoav; Bis Joshua C; Mitchell Braxton D; et al. (OXFORD UNIV PRESS, 2022)
Interleukin 6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67428 (ndiscovery=52654 and nreplication=14774) individuals of European ancestry. The inverse variance fixed effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on chromosome (Chr) 2q14, (Pcombined=1.8x10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (Pcombined=1.5x10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (Pcombined=1.2x10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.